Design of mathematical model of electric car with combined energy supply modes - Попов, Сергей Витальевич; Гуртовой, Михаил Юрьевич (Eastern-European Journal of Enterprise Technologies, 2015)
Modeling of operation modes of the electric car (EC) allows to evaluate important parameters such as driving range, acceleration, battery capacity and type. The task of analysis and modeling of parameters and characteristics of EC with combined energy supply modes is important and of practical interest to developers and car-makers. Currently, the issue of developing EC with combined energy supply modes is not fully disclosed. Also, there are many management strategies of energy storage units (batteries, supercapacitors, fuel cells and their possible combinations). The authors have proposed a mathematical model, which is based on a new algorithm for the power division between the traction battery and the supercapacitor unit in the EC energy supply system. Based on the driving range simulation algorithm, a computing experiment was conducted, followed by analysis of experimental data. Analysis and modeling of the main parameters of EC with combined energy supply modes yielded concrete results of changing the battery life and driving range of EC. The results may be useful for engineering calculations (for example, to search for the optimal values of the energy capacity of the battery and the SC) and improving energy supply systems of electric cars.